2020
DOI: 10.1016/j.ijcha.2020.100643
|View full text |Cite
|
Sign up to set email alerts
|

The Cone Flare Crush Modified-T (CFCT) stenting technique for coronary artery bifurcation lesions

Abstract: Background The present study is a prospective observational single arm clinical investigation, with parallel bench test interrogation, aimed at investigating the technical feasibility, safety and clinical outcomes with the cone flare crush modified-T (CFCT) bifurcation stenting technique. Bifurcation percutaneous coronary intervention (PCI) remains an area of ongoing procedural evolution. More widely applicable and reproducible techniques are required. Methods From Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a recently published paper, we reported the outcomes of a randomized trial comparing DKC with a simplified variant involving a shorter stent crush length and only one rewiring. We reported that this variation, which we called reverse-T-and-protrusion (rTAP) and which resembles a previously reported technique named “cone flare DKC”( 7 ), was non-inferior to DKC in terms of side branch (SB) ostial expansion and was associated with shortened procedural times ( 8 ). In the present study, we compare the intermediate-term outcomes assessed by optical coherence tomography (OCT) of patients with LM bifurcation disease, randomized to either the DKC technique or rTAP.…”
Section: Introductionmentioning
confidence: 77%
“…In a recently published paper, we reported the outcomes of a randomized trial comparing DKC with a simplified variant involving a shorter stent crush length and only one rewiring. We reported that this variation, which we called reverse-T-and-protrusion (rTAP) and which resembles a previously reported technique named “cone flare DKC”( 7 ), was non-inferior to DKC in terms of side branch (SB) ostial expansion and was associated with shortened procedural times ( 8 ). In the present study, we compare the intermediate-term outcomes assessed by optical coherence tomography (OCT) of patients with LM bifurcation disease, randomized to either the DKC technique or rTAP.…”
Section: Introductionmentioning
confidence: 77%
“…An ostial lesion of the coronary artery lies within 3 mm of the opening of the coronary artery [ 1 ]. The lesion is not easy to expand, as it is rich in elastic fiber tissue and easily retracts, and the rate of restenosis and calcification is high.…”
Section: Introductionmentioning
confidence: 99%